1992
DOI: 10.1111/j.1365-2958.1992.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the expression of pili: the effect on adherence of Neisseria meningitidis to human epithelial and endothelial cells

Abstract: The effect of variations in Neisseria meningitidis pili on bacterial interactions with three epithelial cell lines as well as human umbilical vein endothelial cells was studied using a panel of seven strains expressing Class I or Class II pili. Comparison of adherence of piliated and pilus-deficient variants of each strain to epithelial cells suggested that Class I pili may mediate bacterial adherence with all three epithelial cell lines. In contrast, Class II pili of the strains used did not increase bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 23 publications
6
94
0
1
Order By: Relevance
“…The meningococcal capsule is another major surface structure that could hinder intimate contact between Nm and target cells (Virji et al, 1992;de Vries et al, 1996;Hammerschmidt et al, 1996;Hardy et al, 2000). We have previously reported that capsule levels decrease upon cell contact (Deghmane et al, 2000).…”
Section: Modulation Of Capsule and Pili During Adhesion Of Meningococmentioning
confidence: 99%
See 1 more Smart Citation
“…The meningococcal capsule is another major surface structure that could hinder intimate contact between Nm and target cells (Virji et al, 1992;de Vries et al, 1996;Hammerschmidt et al, 1996;Hardy et al, 2000). We have previously reported that capsule levels decrease upon cell contact (Deghmane et al, 2000).…”
Section: Modulation Of Capsule and Pili During Adhesion Of Meningococmentioning
confidence: 99%
“…crgA encodes a transcriptional regulator of the LysR family and seems to be involved in the adhesion of Nm to target cells because insertional inactivation of this gene strongly decreases meningococcal adhesion to epithelial cells, particularly during the phase of Nm-cell intimate adhesion (Deghmane et al, 2000). CrgA may be involved in the switch from initial adhesion to intimate adhesion by downregulating bacterial surface structures that hinder intimate adhesion, such as the pili and capsule (Virji et al, 1992;Hammerschmidt et al, 1996;de Vries et al, 1996;Hardy et al, 2000). The aim of this work was to investigate this hypothesis by analysing the effects of CrgA on the production of pili and capsule during interaction between bacteria and cells.…”
Section: Introductionmentioning
confidence: 99%
“…These data represent the average of three independent experiments. the colonization of epithelial and endothelial cells (Kellogg et al, 1968;Virji et al, 1992). The adherence to epithelial cells is dependent on a pilus adhesin, called PilC, and on variations in the major pilus subunit, PilE (Virji et al, 1992;Nassif et al, 1993;Jonsson et al, 1994;Rudel et al, 1992;1995a,b).…”
Section: Purified Mcp Inhibits Bacterial Bindingmentioning
confidence: 99%
“…the colonization of epithelial and endothelial cells (Kellogg et al, 1968;Virji et al, 1992). The adherence to epithelial cells is dependent on a pilus adhesin, called PilC, and on variations in the major pilus subunit, PilE (Virji et al, 1992;Nassif et al, 1993;Jonsson et al, 1994;Rudel et al, 1992;1995a,b). Our previous studies have shown that piliated N. gonorrhoeae bind to a wide variety of human tissues and cell types and that the receptor is sensitive to proteolysis (Jonsson et al, 1994).…”
Section: Purified Mcp Inhibits Bacterial Bindingmentioning
confidence: 99%
See 1 more Smart Citation